SAKLAR OTOMATIS BERBASIS LIGHT DEPENDENT RESISTOR (LDR) PADA MIKROKONTROLER ARDUINO UNO - Angga Khalifah Tsauqi; Murtezha Hadijaya; Ivander Manuel; Venas Miftah Hasan; Annisa Tsalsabila; Fadhilah Chandra; Titin Yuliana; Putri Tarigan; Irzaman Irzaman (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2016)
Has succeeded in making switch automatic based light dependent resistor ( LDR)in mikrokontroler arduino uno .Switch this tested in two conditions yatu in laboraatrium and in roomy .On condition laboratory , voltage enter of 5.00 volts managed to turn switch , where switch burns in the state of life ( ON ) producing a voltage of 3.74 volts and obstacles of 230 -260 ohm , while switch die ( OFF ) producing a voltage of 4.78 volts and obstacles switch of 44 - 45 ohm , with strong lighting in laboratoium at 15 lux is the verge of a function of switch in the laboratory .On condition in roomy , strong lighting the function switch of 70 lux with obstacles switch equal to 100 ohm .The difference the function obstacles switch this caused by the strong illumination that produced by a lamp in the laboratory compared with strong illumination that produced by the eye day . Kata kunci: saklar otomatis, LDR, mikrokontroler,kuat penerangan, lux.